Climate-Sensitive Management of Public Finances : "Green PFM" - Gonguet, Fabien (International Monetary Fund, 2021)
Public financial management (PFM) consists of all the government's institutional arrangements in place to facilitate the implementation of fiscal policies. In response to the growing urgency to fight climate change, 'green PFM' aims at adapting existing PFM practices to support climate-sensitive policies. With the cross-cutting nature of climate change and wider environmental concerns, green PFM can be a key enabler of an integrated government strategy to combat climate change. This note outlines a framework for green PFM, emphasizing the need for an approach combining various entry points within, across, and beyond the budget cycle. This includes components such as fiscal transparency and external oversight, and coordination with state-owned enterprises and subnational governments. The note also identifies principles for effective implementation of a green PFM strategy, among which the need for a strong stewardship located within the ministry of finance is paramount.